CHARISMATIC AUTHORITY IN THE TRADITION OF READING HIZB HIRZ AL-JAUSHAN AT PESANTREN HIDAYATUL MUBTADI-AAT - Millati, Halya; Qudsia, Miatul (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2020)
Muslim society’s acceptance of a hadith is manifested in many behaviors, one of which is the use of the hadith sentences as a prayer and dhikr that manifests in a ḥizb. The hadith used as part of the ḥizb is a hadith containing prayers taught by Allah to the Prophet during the battle of Uhud. This hadith is known as the Jawshân Hadith, so the ḥizb born from the act of interpreting the hadith is called the ḥizb Ḥirz al-Jawshân. This study aims to find motives that encourage the community, especially students at Pesantren Hidayatul Mubtadi-aat, in the reception of the hadith in the form of ḥizb reading. To achieve this purpose, this study uses a field study method using Marx Weber’s charismatic authority approach. This research found that the reading, which was done by santri Hidayatul Mubtadi-aat, was a form of performative effort on Jawshân hadith. This is based on a shift in the understanding of the hadith from the informative function to the performative function in the time of al-Ḥusayn. The reading, which was done by santri Hidayatul Mubtadi-aat, was not caused by their understanding of the hadith content, but rather due to the encouragement from outside of themselves to accept the hadith. The encouragement comes from Kiai, who has a charismatic factor so that santri submit and obey without knowing the reasons for the order.